Synergistic Effects of Aerobic Exercise and Moringa Oleifera Supplementation on Glycemic Control and Metabolic Health in Type 2 Diabetes Patients: A Randomized Controlled Trial - Muhammed, Jwan Abbas; Ahmed, Diyar Maghdid; Othman, Goran (South Eastern European Journal of Public Health, 2024)
Background: The action of aerobic exercise and Moringa Oleifera supplementation on type 2 diabetes mellitus (T2DM) have been individually documented, but their combination remains unclear. This study evaluates the synergistic effects of a 12-week aerobic exercise program and Moringa supplementation on metabolic and inflammatory markers in T2DM patients. Methods: A total of 120 T2DM patients were randomly assigned to four groups: control, aerobic exercise, moringa supplementation (250mg/kg/day), and a combination. BMI, blood glucose, serum insulin, serum C-peptide, renal function tests, HbA1c, adiponectin, IL-6, and lipid profile, were assessed before and after the intervention. Blood glucose levels were monitored weekly. Results: All intervention groups showed significant improvements in HbA1c levels compared to the control group, with the combination group demonstrating the greatest reduction. Blood glucose levels decreased significantly in the exercise and combination groups, with the aerobic exercise group outperforming moringa alone. Serum insulin levels significantly decreased in the moringa and combination groups, while serum C-peptide levels decreased in all groups. Lipid profile improvements were noted in all intervention groups, with the combination treatment showing superior results in reducing total cholesterol and BMI. Both adiponectin levels increased and IL-6 levels decreased significantly in all intervention groups, particularly in the combination group. Renal function tests showed no adverse changes, with a significant reduction in BUN levels observed only in the combination group. Conclusion: The combination of aerobic exercise and moringa supplementation provides a synergistic therapeutic effect, significantly improving glycemic control, lipid profile, adiponectin levels in T2DM patients.